2019
DOI: 10.1016/j.atherosclerosis.2019.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Subjects with diffuse idiopathic skeletal hyperostosis have an increased burden of coronary artery disease: An evaluation in the COPDGene cohort

Abstract: idiopathic skeletal hyperostosis (DISH) is a common incidental finding on medical imaging and often thought to be benign.• Subjects with DISH have more CAC as a reflection of coronary atherosclerosis.• DISH is usually observed as an incidental finding on imaging and may be an important finding to stimulate assessment of occult cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
(33 reference statements)
2
15
0
1
Order By: Relevance
“…Although the exact pathophysiology of DISH remains undetermined to date, metabolic factors with low-grade inflammation are thought to contribute to ossification in the disease as DISH has been frequently associated with hyperinsulinemia, type 2 diabetes, obesity, and hypertension ( Mader et al, 2013 ; Mader et al, 2021 ; Harlianto et al, 2021 ). Furthermore, intracerebral and coronary calcifications have also been reported to be increased in patients with DISH ( Mader et al, 2013 ; Oudkerk et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathophysiology of DISH remains undetermined to date, metabolic factors with low-grade inflammation are thought to contribute to ossification in the disease as DISH has been frequently associated with hyperinsulinemia, type 2 diabetes, obesity, and hypertension ( Mader et al, 2013 ; Mader et al, 2021 ; Harlianto et al, 2021 ). Furthermore, intracerebral and coronary calcifications have also been reported to be increased in patients with DISH ( Mader et al, 2013 ; Oudkerk et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcifications are considered to be a strong risk factor for adverse cardiovascular outcomes. It has recently been shown that patients with DISH have a significantly higher risk of having coronary artery calcifications, even after correction for age, gender, and atherosclerotic risk factors [29]. Thus, DISH itself may contribute to the CVD risk burden.…”
Section: Discussionmentioning
confidence: 99%
“…diabetes mellitus, obesity, hypertension) has been documented previously (7)(8)(9). Increasing evidence is emerging about the presence of a common pathogenic substrate for metabolic syndrome-associated disorders (including atherosclerosis) and the process of new bone formation in patients with DISH (6,10,19). In fact, approximately half of the patients in the current study had a history of ischaemic cardiovascular events, with a high prevalence of hypertension (57.4%) and diabetes mellitus (34.8%) and a mean BMI of 27.9 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%